2019
DOI: 10.1155/2019/3264858
|View full text |Cite
|
Sign up to set email alerts
|

The NADPH Oxidase Nox4 Controls Macrophage Polarization in an NFκB-Dependent Manner

Abstract: The family of NADPH oxidases represents an important source of reactive oxygen species (ROS) within the cell. Nox4 is a special member of this family as it constitutively produces H2O2 and its loss promotes inflammation. A major cellular component of inflammation is the macrophage population, which can be divided into several subpopulations depending on their phenotype, with proinflammatory M(LPS+IFNγ) and wound-healing M(IL4+IL13) macrophages being extremes of the functional spectrum. Whether Nox4 is expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 32 publications
2
44
0
Order By: Relevance
“…Evidence exists that ROS production is enhanced in M1-like Mac compared to either resting or M2-like Mac [43]. Yet, the precise role and regulation of Nox expression in different Mac subsets is not entirely understood.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence exists that ROS production is enhanced in M1-like Mac compared to either resting or M2-like Mac [43]. Yet, the precise role and regulation of Nox expression in different Mac subsets is not entirely understood.…”
Section: Resultsmentioning
confidence: 99%
“…However, in some cancer cell types, ADP-ribosylation emerged as an repressor of NOX1 and NOX4 since cell treatment with PJ34 resulted in upregulation of NOX1 and NOX4 mRNAs [ 114 ]. The latter enzyme plays a role in defining the macrophage phenotype and the direction of their polarization [ 115 ]. NOX4 promotes the development of anti-inflammatory phagocytes by the induction of STAT6 and, as a consequence, the reduction of NFκB activity.…”
Section: Parp1 In Macrophages—its Role In Their Polarizationmentioning
confidence: 99%
“…We discovered a striking association between NOX2 and macrophage signatures that strongly suggests that the major source of NOX2 is derived from TAMs ( Figure 5 ). Although NOX2 is considered the primary source of ROS in macrophages, recent studies revealed that other less abundant NOX enzymes can affect the fate and function of macrophages, including DUOX1, NOX1 and NOX4 [ 42 , 43 , 44 ]. For example, studies with Nox1/Nox2 double-knockout mice suggest both oxidases support monocyte differentiation into macrophages [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, studies with Nox1/Nox2 double-knockout mice suggest both oxidases support monocyte differentiation into macrophages [ 43 ]. Furthermore, observations with Nox4 knock-out mice indicate the absence of Nox4 results in several proinflammatory phenotypes, including increased macrophage Nox2 expression and enhanced infiltration of proinflammatory macrophages in tumors of an induced fibrosarcoma model [ 44 ]. Taken together, we must consider that TAM and TAM-derived NOX2 are linked to the aforementioned genetic programs of cancer progression, and that this may, in part, involve a direct interplay between Nox2 and Nox4 within TAMs.…”
Section: Resultsmentioning
confidence: 99%